2023
DOI: 10.1177/08987564231159805
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dental and Oral Pathologies of 36 Captive Lions (Panthera leo) and Tigers (Panthera tigris)

Abstract: The documented increase in the occurrence of dental diseases in captive big cats over the past decades has necessitated the need to target dental medical research accordingly. The aim of this study was the systematic evaluation of dental and oral pathologies of lions and tigers which included intraoral dental radiography. Thirty-six animals of both sexes, ranging in age from nine months to 18 years, predominantly in circus husbandry, served as the basis of the present study, and their dental health status was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Large carnivores in sanctuaries or zoos often experience dental damage owing to their habits such as chewing on the steel bars of enclosures or environmental influences [ 1 ]. A recent survey of oral examinations of captive lions and tigers revealed that dentoalveolar trauma, such as tooth fracture and abrasion, was present in 66.7% of the cases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Large carnivores in sanctuaries or zoos often experience dental damage owing to their habits such as chewing on the steel bars of enclosures or environmental influences [ 1 ]. A recent survey of oral examinations of captive lions and tigers revealed that dentoalveolar trauma, such as tooth fracture and abrasion, was present in 66.7% of the cases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…15,22 Dental disease, which is one of the most commonly reported causes of morbidity in captive nondomestic felids, often goes undetected for extended periods of time. 16,20 Dental disease, which is a broad term that typically refers to various lesions of the teeth (e.g., abrasion, tooth fracture, dental calculus), is often associated with other types of oral pathology, such as inflammation of the surrounding soft tissue(s) (e.g., periodontitis, gingivitis). Given the prevalence of chronic inflammatory conditions within the oral cavity of domestic felids, a similar relationship between chronic inflammation and oral neoplasia in other cats has been postulated.…”
mentioning
confidence: 99%
“…Systemic evaluation of the oral cavity (including examination awake and under anesthesia, and intraoral dental radiographs) may facilitate early detection of dental disease and SCC. 16…”
mentioning
confidence: 99%